Age of Sexual Debut and Physical Dating Violence Victimization: Sex Differences Among US High School Students. (March 2017) - Ihongbe, Timothy O.; Cha, Susan; Masho, Saba W.
ABSTRACT: BACKGROUND: Research has shown that early age of sexual debut is associated with physical dating violence (PDV), but sex‐specific associations are sparse. We estimated the prevalence of PDV victimization in high school students who have initiated sexual intercourse and examined sex‐specific association between age of sexual debut and PDV victimization. METHODS: Data on 8637 students in grades 9 through 12 who had initiated sex was obtained from the 2009‐2011 national Youth Risk Behavior Survey. The association was examined using multiple logistic regression, accounting for the complex survey design, and stratified by sex. RESULTS: Approximately 15% of sexually active students reported past‐year PDV victimization. The odds of PDV victimization among girls who had sexual debut at <12 years was 2.46 (95% CI = 1.50‐4.02) and 2.20 (95% CI = 1.42‐3.41) for boys, compared to those who initiated sex at 16 years and older. CONCLUSIONS: Evidence supports the belief that early sexual debut is associated with higher odds of PDV victimization, particularly for girls. Healthcare providers, school counselors, and educators should be aware of this sex difference in the association between early sexual debut age and PDV victimization while focusing PDV interventions on adolescents with early sexual debut age.